Mortality in captive baboons (Papio spp.): a‐23‐year study. Issue 3 (1st February 2014) - Dick, Edward J.; Owston, Michael A.; David, John M.; Sharp, R. Mark; Rouse, Scott; Hubbard, Gene B.
Abstract Background We report the causes of mortality for 4350 captive baboons that died or were euthanized due to natural causes during a 23 year period at the Southwest National Primate Research Center. Methods Necropsy records were retrieved and reviewed to determine a primary cause of death or indication for euthanasia. Data was evaluated for morphological diagnosis, organ system, and etiology. Results The 20 most common morphologic diagnoses accounted for 76% of the cases, including stillborn (10.8%); colitis (8.6%); hemorrhage (8.4%); ulcer (5.2%); seizures (4.7%); pneumonia (4.2%); inanition (4.1%); dermatitis (3.8%); spondylosis (3.3%); and amyloidosis (3.0%). The digestive system was most frequently involved (21.3%), followed by the urogenital (20.3%), cardiovascular (12.2%), and multisystem disease (10.3%). An etiology was not identified in approximately one‐third of cases. The most common etiologies were trauma (14.8%), degenerative (9.5%), viral (8.7%), and neoplastic/proliferative (7.0%). Conclusion This information should be useful for individuals working with baboons.